Juridical Review On Notarical Testament In The Perspectives Of Islamic Inheritance Law - Galih Mahendratama Putra; Adad Adad; Gunarto Gunarto (Jurnal Akta, 2018)
Most of Indonesian is aware of law in aspects of life, including inheritance distribution. Every parent with children does not want to let his heirs disagreed or conflicted in terms of inheritance after he passed away. Thus a testament is made to fairly distribute inheritance. Among reasons to compile testament deed are testator intentions to make his property useful for better purposes, i.e. to get closer to Allah SWT The Most Merciful. He also expects himself to perceive true faith and devotion to God, as well as to open fortune door to all recipients. However there may occur obstacle in distributing inheritance. Since civil law regarding testament is different from Islamic faraid law in some aspect.Keywords: Testament; Notary; Inheritance.